The stone child - Poblocki, Dan (Random House, 2009)
When friends Eddie, Harris, and Maggie discover that the scary adventures in their favorite author's fictional books come true, they must find a way to close the portal that allows evil creatures and witches to enter their hometown of Gatesweed.